2004
DOI: 10.1177/001698620404800406
|View full text |Cite
|
Sign up to set email alerts
|

Reading Instruction for Talented Readers: Case Studies Documenting Few Opportunities for Continuous Progress

Abstract: In this study, a team of researchers conducted multiple observations in 12 third- and seventh-grade reading classrooms in both urban and suburban school districts over a 9-month period. These observations focused on whether talented readers received differentiated reading curriculum and/or instructional strategies. Talented readers were defined as students reading at least two grades above their chronological grade placement who also had advanced language skills and advanced processing capabilities in reading.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(117 citation statements)
references
References 30 publications
1
112
2
Order By: Relevance
“…Current research suggests that gifted and talented students fail to be challenged in school, especially in elementary and middle school Reis et al, , 2004Westberg, Archambault, Dobyns, & Salvin, 1993). Research conducted by researchers at the National Research Center on the Gifted and Talented has identified what occurs in American classrooms for high ability students and the results describe a disturbing pattern .…”
Section: Continuing Absence Of Challenge For Gifted and Talented Studmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research suggests that gifted and talented students fail to be challenged in school, especially in elementary and middle school Reis et al, , 2004Westberg, Archambault, Dobyns, & Salvin, 1993). Research conducted by researchers at the National Research Center on the Gifted and Talented has identified what occurs in American classrooms for high ability students and the results describe a disturbing pattern .…”
Section: Continuing Absence Of Challenge For Gifted and Talented Studmentioning
confidence: 99%
“…Almost all classroom teachers learned to use compacting, but needed coaching and help to substitute appropriately challenging options. Reis et al (2004) Reading instruction for talented readers: Case studies documenting few opportunities for continuous progress N = 12 teachers; N = 350 students E, M Research was conducted in 12 different third and seventh grade reading classrooms in both urban and suburban school districts over a 9-month period. Results indicated that little purposeful or meaningful differentiated reading instruction was provided for talented readers in any of the classrooms.…”
Section: Continuing Absence Of Challenge For Gifted and Talented Studmentioning
confidence: 99%
“…The first author classified students identified as reading two or more years above their chronological age as the gifted sample group, in line with current research definitions (Moore, 2005;Reis et al, 2004). Teachers simply provided an expectation for each child in the class, and had the option of commenting about particular students' special learning needs or abilities in reading .…”
Section: Discussionmentioning
confidence: 99%
“…Standardised reading achievement data for every student were compared to national means. Of the students, 275 were identified as reading 2 or more years above their chronological age, and were classified as gifted in accordance with the definition of Reis et al (2004), and 1413 students were identified as nongifted. Although there was a relatively even gender split of 821 boys (48.6%) and 867 girls (51.4%) across the total sample of 1688 student participants, within the sample group of gifted readers, 58.9% were girls (n = 162) and 41.1% were boys (n = 113).…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation